PENGARUH PEMBERIAN SENAM KEGEL UNTUK MENURUNKAN DERAJAT INKONTINENSIA URIN PADA LANSIA - Yulia Tetra Ilona; Nova Relida (Jurnal Ilmiah Fisioterapi, 2020)
Background. Urinary incontinence by the international continents society (ICS) defines it as a condition in which uncontrolled urine output is a social or hygienic problem in the elderly and can be proven objectively. Purpose. This study aimed at patients with urinary incontinence to improve pelvic floor muscles. Physiotherapy interventions that can be given to patients with urinary incontinence in dealing with decreased function in the pelvic floor muscles can be done with a variety of actions including the administration of Kegel exercises. Research methods. The research conducted is a case study with a pre and post test research design. Results. The results of the study in sample I obtained changes in improvement in pelvic floor muscle described by changes in the scale of RUIS at T0 score value of 15 and at score T12 obtained score 10. In sample II obtained changes in improvement at T0 score value 13 and at T12 score obtained 10. Then in the sample III obtained changes in improvement. At T0 the score of 15 and at T12 obtained a score of 9.